Adsorption of Mercury (II) Ions from Water Using Carbon-Based Monolith with Manganese Oxide Filler - Kusuma, Debby Widya; Mahidin, Mahidin; darmadi, darmadi (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2022)
Mercury is harmful to humans and the ecological environment. The adsorption process is known as an effective method for removing heavy metals. This research is devoted to developing new adsorbents based on carbon materials to remove metal ions Hg(II) with carbon-based monolith adsorbents without and with manganese oxide fillers (KM and KMM). The results of adsorption efficiency, adsorption kinetics, and isotherm models were made in a batch system with varying concentrations of mercury solution from 2 mg/L to 6 mg/L with adsorbents without and with manganese oxide fillers (KM and KMM). The highest removal efficiency reached 96% on KMM and 47% on KM. The adsorption isotherm of Hg(II) ions corresponds to the Freundlich model, with intensity and volume constants obtained respectively 0.042 and 1.347 L/mg on KM adsorbents, while on KMM adsorbents the intensity and volume constants obtained are 0.291 and 2.079, respectively. L/mg. These results indicate that physical adsorption occurs more dominantly than chemical adsorption. The adsorption of Hg(II) ions was in accordance with the pseudo-first-order adsorption kinetics, with the adsorption capacity and rate constant on the KM adsorbent obtained were 0.0505 mg/g and 0.0072 g/mg, while the adsorption capacity and rate constant for the KMM adsorbent were on KM adsorbents obtained were 0.0848 mg/g and 0.0239 g/mg.